Constrained Consumers: Middle-Class Parents' Resistance of School Closure and Consolidation in Chicago. Issue 9 (December 2020) - Wright-Costello, Beth; Phillippo, Kate
Many urban districts use a portfolio management model, hoping to promote school choice and improve school performance. This model requires school closure, which has predominantly impacted lower income families. In 2013, Chicago Public Schools relocated Granger Elementary into one of 48 schools it closed, placing its middle-class parents in the unusual position of resisting a school closure-related decision. Our case study explores parents' resistance from a perspective of capital use and parental agency. Interview participants leveraged extensive capital in response to the proposed closure–relocation. When their efforts failed to halt the directive, they used their resources as consumers, largely finding their children spaces in other schools. Parents were unable to effectively exercise agency to influence district-level policy, but they secured educational advantages for their own children by leveraging their capital. Findings inform implications for market-based policy theory, equity, and democratic control of public schools.